Eliciting experts' knowledge in emergency response organizations. Issue 2 (7th October 2014) - Okechukwu Okoli, Justin; Weller, Gordon; Watt, John
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Experienced fire ground commanders are known to make decisions in time-pressured and dynamic environments. The purpose of this paper is to report some of the tacit knowledge and skills expert firefighters use in performing complex fire ground tasks. Design/methodology/approach – This study utilized a structured knowledge elicitation tool, known as the critical decision method (CDM), to elicit expert knowledge. Totally, 17 experienced firefighters were interviewed in-depth using a semi-structured CDM interview protocol. The CDM protocol was analysed using the emergent themes analysis approach. Findings – Findings from the CDM protocol reveal both the salient cues sought, which the authors termed critical cue inventory (CCI), and the goals pursued by the fire ground commanders at each decision point. The CCI is categorized into five classes based on the type of information each cue generates to the incident commanders. Practical implications – Since the CDM is a useful tool for identifying training needs, this study discussed the practical implications for transferring experts' knowledge to novice firefighters. Originality/value – Although many authors recognize that experts perform exceptionally well in their domains of practice, the difficulty still lies in getting a structured method for unmasking experts' tacit knowledge. This paper is therefore relevant as it presents useful findings following a naturalistic knowledge elicitation study that was conducted across different fire stations in the UK and Nigeria.